Dispute Resolution in Unwritten Agreements in Connection of Cooperation Reviewed from a Civil Law Perspective - Ria Juliana Siregar; Martono Anggusti; Rio Saputra Manullang (Sultan Agung Notary Law Review, 2026)
This study aims to describe the regulation of agreements according to Indonesian contract law (KUHPerdata), which then analyzes the legal force of agreements made orally and their proof in court. This research is a normative juridical research conducted with a statutory and conceptual approach. The results of the study indicate that agreements are specifically regulated in the Civil Code, Book III, Chapter II concerning "Agreements Born from Contracts or Agreements" and Chapters V to XVIII which regulate the legal principles and norms of contract law in general, as well as contract law norms that have special characteristics better known as named agreements. The Civil Code itself does not explicitly mention "written agreements". If an oral agreement has fulfilled the requirements for a valid agreement according to the formulation of Article 1320 of the Civil Code, then it remains valid and has legal force to declare someone in default. However, if the verbal agreement is denied/not acknowledged by the party suspected of being in breach of contract, the verbal agreement does not have legal force to declare someone to be in breach of contract, because the agreement may or may not be true, depending on the evidence provided by the parties.